The Rise of Populist Narratives and Military Coups in Africa: A Pan-African Perspective on People's Power and Democratic Reversals - Fagha, Munjah Vitalis (Advances in Social Sciences Research Journal, 2025)
Since the early 2000s, Africa has experienced a troubling comeback of military coups and the rise of populist narratives that threaten to reverse decades of democratic advancement. This paper investigates the structural and political conditions encouraging this drift, focusing on countries such as Mali, Guinea, Burkina Faso, and Niger, where military actors have justified unconstitutional takeovers by invoking “people’s power.” The paper aims to explore how populist rhetoric is used to legitimize anti-democratic actions and assess the responses of regional bodies like ECOWAS and the African Union. Adopting a qualitative, comparative case study approach, the research draws on content analysis of policy documents, speeches, and media reports, guided by a framework combining democratic theory and populism studies. Findings reveal that weak institutions, poor governance, corruption, and socioeconomic discontent have created fertile ground for populist-military alliances. Military leaders often portray themselves as corrective agents of the people's will, blurring the line between democratic restoration and authoritarian consolidation. Meanwhile, regional bodies have shown normative commitment to democracy but limited enforcement capacity. The paper concludes that the manipulation of populist narratives undermines constitutionalism and legitimizes undemocratic rule. It underscores the need for stronger democratic institutions, inclusive governance, and more effective regional enforcement mechanisms. These findings have significant implications for democratic resilience in Africa and highlight the urgency of rethinking how "people's power" is defined and safeguarded in transitional societies.